STUDENTS’ AND PARENTS’ PERCEPTIONS TOWARD ENGLISH E-LEARNING DURING THE COVID-19 PANDEMIC - Maulinda Fani Ramlah; Zuhad Ahmad (UICELL, 2022)
For last two years, we all got affected by Covid-19 virus global outbreak that harmed our daily activities’ life, including in education matters. In that pandemic situation, the use of technology became so dominant, and it forced students and teachers to still do teaching and learning through e-learning tools. This research focused on the questioning of students’ and parents’ perceptions toward English e-learning during Covid-19 pandemic in the past two years (2020-2021). The respondents were the students on Elementary School in which e-learning process required the role of parents to assist their children during learning significantly. Hopefully, this research may find out how students and parents viewed towards the discussion of English e-learning utilization during the Covid-19 pandemic. The method of this research was qualitative, with the use of interview instrument. The respondents were 30 students and 30 students’ parents of SDN Rawa Badak Utara 01 Jakarta. The findings showed that most of the perception given by students and parents regarding English e-learning were quite positively in content of effectiveness of teaching and learning process from home. However, it found information that some students and their parents had major difficulties in accessing e-learning technology, problems in internet connection or network, issue with the economy such as internet quota cost, and etc. Keywords: English E-Learning, Perception, Covid-19 Pandemic